2022
DOI: 10.1186/s13098-022-00817-w
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in T1DM patients after high-dose cholecalciferol supplementation: data from a pilot clinical trial

Abstract: Background Type 1 Diabetes Mellitus (T1DM) impacts health-related quality of life (HRQoL). Cross-sectional studies suggest that low levels of vitamin D (VD) may impair HRQoL, however, the effect of VD supplementation on quality of life in T1DM patients has not yet been clarified. Our study evaluated the effects of high-dose VD supplementation on HRQoL in T1DM. Methods We performed a prospective study with 64 patients receiving cholecalciferol (4000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The main extra-skeletal action of vitamin D is exerted into the cell nucleus which revealed its ability to regulate the transcription of approximately the 3% of the human genome. 25(OH)D deficiency represents a major health problem since it has been related to cardiovascular, inflammatory, autoimmune diseases, and cancer and development of DMT1 as well as diabetes-associated secondary osteoporosis [2,3]. The relationship between the bioavailability of vitamin D, its metabolism, and T1D development is multifactorial and is confirmed by genetic studies in humans.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The main extra-skeletal action of vitamin D is exerted into the cell nucleus which revealed its ability to regulate the transcription of approximately the 3% of the human genome. 25(OH)D deficiency represents a major health problem since it has been related to cardiovascular, inflammatory, autoimmune diseases, and cancer and development of DMT1 as well as diabetes-associated secondary osteoporosis [2,3]. The relationship between the bioavailability of vitamin D, its metabolism, and T1D development is multifactorial and is confirmed by genetic studies in humans.…”
Section: Introductionmentioning
confidence: 97%
“…3 shows the comparison in investigation results between study groups. Means of FBS, HbA1c, B. urea, and albuminuria were significantly higher (P < 0.05) in group A than that in groups B and C. Means of S.Ca, S. albumin, and GFR were significantly low (P < 0.05) in group A than that in groups B and C. No statistical significant difference in mean of s. creatinine between study groups (P= 0.083).Figure 4.2.vitamin D level in study groupsAs shown in table (4.4), Mean of vitamin D was significantly lower (19.13, P = 0.001) in diabetic patients with NP (Group A) than that in diabetic patients without NP (Group B) and healthy subjects (Group C).…”
mentioning
confidence: 99%